The ethics of neoliberalism : the business of making capitalism moral - Bloom, Peter (Social science teacher) (Routledge studies in business ethics ;, 2017)
"The 21st century is the age of "neo-liberalism"--A time when the free market is spreading to all areas of economic, political and social life. Yet how is this changing our individual and collective ethics? Is capitalism also becoming our new morality? From the growing popular demand for corporate social responsibility to personal desire for "work-life balance" it would appear that non-market ideals are not only surviving but also thriving. Why then does it seem that capitalism remains as strong as ever?The Ethics of Neoliberalism boldly proposes that neoliberalism strategically co-opts traditional ethics to ideologically and structurally strengthen capitalism. It produces "the ethical capitalist subject" who is personally responsible for making their society, workplace and even their lives "more ethical" in the face of an immoral but seemingly permanent free market. Rather than altering our morality, neoliberalism "individualizes" ethics, making us personally responsible for dealing with and resolving its moral failings. In doing so, individuals end up perpetuating the very market system that they morally oppose and feel powerless to ultimately change. This analysis reveals the complex and paradoxical way capitalism is currently shaping us as "ethical subjects". People are increasingly asked to ethically "save" capitalism both collectively and personally. This can range from the "moral responsibility" to politically accept austerity following the financial crisis to the willingness of employees to sacrifice their time and energy to make their neoliberal organizations more "humane" to the efforts by individuals to contribute to their family and communities despite the pressures of a franetic global business environment. Neoliberalism, thus, uses our ethics against us, relying on our "good nature" and sense of personal responsibility to reduce its human cost in practice. Ironically"--Provided by publisher.